Strategi Inkubator Bisnis Dalam Pengembangan Startup Digital - Arini Zahrah Nasyiah Makkawaru; Risnawati Risnawati; Harnida Wahyuni Adda; Fera Fera (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
A startup is a start-up business that creates new products or services and is founded by a group of individuals to find a new business model or service in the dynamics of a developing market. Indonesia is a country with a world startup ranking percentage that occupies 6th position, but data shows that the startup failure ratio is very high. Based on the phenomenon of startup problems that occur, systematic steps are needed in developing startups so that research is prepared in the form of designing startup development strategies through business incubators. The method used in this report is a qualitative method which is descriptive and analytical. To collect data in this research, researchers used observation, interviews and documentation methods, while the data analysis techniques used in this research were; data reduction, data presentation, and drawing conclusions/verification. The strategy prepared by the IBTI Maleo Techno Center to encourage startup development by using targeted steps also looks at several aspects, namely development/management capability aspects, financial aspects, marketing aspects and human resource aspects. This is planned to create long-term business success.